Juridical Review The Implementation of Oral Agreement is associated with the Law of Treaties and Law Number 8 Year 1999 concerning Consumer Protection - Dian Eka Pusvita Azis; Nurhaedah Nurhaedah (Faculty of Law, Universitas Muslim Indonesia, Indonesia, 2018)
The covenant is one of the most common legal relationships in the community. The Covenant under Article 1313 of the Civil Code is an act by which a person or more binds himself to one or more persons. Unconsciously, oral agreements are often done in social life and often the parties who make the oral agreement deny the existence of the agreement. This research is descriptive normative juridical research. This study uses primary legal material sources consisting of laws and regulations bound by research. Sources of secondary legal materials in the form of materials or related materials and explain the problem, and the source of tertiary legal materials are materials that provide information about primary legal materials and secondary legal materials related to the research. Against the form of the exercise of the agreement in the oral form declared unilaterally by the party that offers the agreement inevitably the interested party in this case the second party is pressed with the interest of agreeing the contents of the agreement. Not to mention the possibilities that occur in the future that is wanprestasi with large losses so that the court to face, and what if the party who did the default is negligent, broken promise, do not acknowledge or deny having oral agreement Based on the background and problems that have been described above so it is necessary to examine the extent to which the legal protection of oral agreements, if one of the parties making the alleged infringement of the oral agreement is associated with the Law of Contract and the Consumer Protection Number Act. Based on this research it is concluded that the oral agreement is legal and has the legal power to declare a person to default, but if the oral agreement is denied / not recognized by the alleged defendant, the oral agreement has no legal power to declare a person to default, can be true and may not exist, depending on the proof of the parties. but verbal agreements that have been denied / unrecognized may regain their legal power if it can be proven that the oral agreement actually exists or has been made.Based on Law No. 8 Consumer Protection Consumer law is defined as the whole legal principles and rules governing relationships and problems between various parties or each other in relation to goods and / or services within the association of life. Based on Article 163 HIR and Article 1865 of the Civil Code, any party that argues for a right, then the party must prove it. So if the consumer demands his right to the business actor that harms him, then the consumer must prove. However, in Law Number 8 Year 1999 concerning Consumer Protection Article 22 and Article 28, the evidentiary obligation is